2017
DOI: 10.1039/c7ob90088k
|View full text |Cite
|
Sign up to set email alerts
|

Correction: nBu4NI-Mediated oxidation of methyl ketones to α-ketoamides: using ammonium, primary and secondary amine-salt as an amine moiety

Abstract: Correction for 'nBuNI-Mediated oxidation of methyl ketones to α-ketoamides: using ammonium, primary and secondary amine-salt as an amine moiety' by Dan Wang et al., Org. Biomol. Chem., 2017, 15, 3427-3434.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Lin and co‐workers [54] employed thiols as precursors of N ‐thiopyrrolidine 41.1 in the presence of NBS. The thirranium formation and ring‐opening addition strategy worked well for the thiolation‐amidation 41.2 of alkenes.…”
Section: Thiolationmentioning
confidence: 99%
“…Lin and co‐workers [54] employed thiols as precursors of N ‐thiopyrrolidine 41.1 in the presence of NBS. The thirranium formation and ring‐opening addition strategy worked well for the thiolation‐amidation 41.2 of alkenes.…”
Section: Thiolationmentioning
confidence: 99%
“…Song and Chen research groups revealed that PIDA oxidation in conjunction with an AgSbF 6 catalyst allowed for the selective C−H selenylation of indole scaffolds ( 231 ) at the C5 position, resulting in the creation of a variety of otherwise challenging to prepare 5‐selenylated indole derivatives ( 232 ) (Scheme 81). [161] The tethered C3 pivaloyl group on indole scaffolds had a function in both blocking the active C3 position and adjusting the electrical affinity of the arenes, according to mechanistic investigations, which showed that current transformation follows a radical process.…”
Section: Applications Of Phenyliodine(iii)diacetatementioning
confidence: 99%
“…α ‐Ketoamides have attracted considerable interest due to their potential ability as versatile synthetic motifs in numerous natural products, biological drug candidates and functional group transformations . Various approaches have been proposed in the synthesis of a diverse array of α ‐ketoamides from different ketones and amines . Recently, the iodine‐driven reaction have emerged as a powerful strategy because of the particularly reactive halogen bond‐based systems.…”
Section: Introductionmentioning
confidence: 99%
“…In classical amidations with the addition of iodine (I 2 ), the amine is recognized as the reactant, and I 2 is almost presumed to play the catalytic role . Our previous studies reported the preparation of diverse α ‐ketoamides under clean and mild conditions from varying substrates including aryl methyl ketones . Currently, there are two issues involved with the direct amidation.…”
Section: Introductionmentioning
confidence: 99%